Assessing the anxiety profile of patients undergoing hysterectomy and mastectomy - Manahan, Lydia T.
Cancer is threatening to many. By the mere mention of the word, anxiety runs down every nerve of any individual regardless of age, creed, race, or sex. Psychosocially, the individual is thrown off balance when diagnosis of cancer is confirmed. Once cancer is diagnosed as the ailment, surgery becomes the most popular intervention often recoursed to by cancer clients. Surgery becomes another psychoniological threat. This causes anxiety because it is an invasive intervention. To profile the anxiety level of clients who had been diagnosed with cancer and who had undergone surgical interventions, this study was conducted with an attempt to answer the following problems questions: 1. What is the anxiety profile of clients who have undergone hysterectomy and mastectomy? 2. Is there a relationship between the clients' manifested level of anxiety and their demographic variables, such as age, educational attainment, civil status, socioeconomic status, and religiosity? 3. Is there level of manifested anxiety related to women's variables such as her role as wife, as mother, and as a house manager? 4. Is the level of manifested anxiety related to the client's medical variables such as tyoe of surgery and length of hospitalization? 5. Is the level of manifested anxiety related to the clients' interpersonal relationship variables i.e. nurse-patient, doctor-patient in informed consent? 6. Is the level of manifested anxiety related to the clients' social support such as the number of persons extending support and the type of support provided? 7. Is there a significant difference in the levels of manifested anxiety between mastectomy and hysterectomy clients the effects of their surgery? These questions leaned on the conceptual framework that anxiety level of clients with cancer and who underwent surgery are affected by several factors grouped according to: - personal sociodemographic characteristics. - women's variables. - medical variables. - interpersonal relationships, and - social support.